2007
DOI: 10.1007/s11274-007-9502-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of Sclerotium rolfsii with integration of non-conventional chemicals, vermicompost and Pseudomonas syringae

Abstract: Two non-conventional chemicals, ZnSO 4 (10 À4 mM) and oxalic acid (4 mM) were tested (alone as well as in combination with seeds bacterized with Pseudomonas syringae strain PUR46 and vermicompost substitution in the potting soil), for their ability to suppress collar rot of chickpea (Cicer arietinum) caused by Sclerotium rolfsii under greenhouse conditions. ZnSO 4 and oxalic acid were applied as pre-inoculation foliar spray on chickpea and subsequently challenged with S. rolfsii. Both the chemicals provided si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…This increase could be related to the rule of Fe-EDTA in promoting plant growth and subsequently P content. Previous work by Egamberdiyeva (2007) using Bacillus and Pseudomonas on maize, Sahni et al (2008) with the use of Pseudomonas syringae on chickpea, and Fernandez et al (2007) using solubilizing PGPR on soybean, found similar responses. The increase of K content due to the use of these PGPR is the result of biomass increase of plants.…”
Section: Discussionmentioning
confidence: 63%
“…This increase could be related to the rule of Fe-EDTA in promoting plant growth and subsequently P content. Previous work by Egamberdiyeva (2007) using Bacillus and Pseudomonas on maize, Sahni et al (2008) with the use of Pseudomonas syringae on chickpea, and Fernandez et al (2007) using solubilizing PGPR on soybean, found similar responses. The increase of K content due to the use of these PGPR is the result of biomass increase of plants.…”
Section: Discussionmentioning
confidence: 63%
“…Vermicompost promotes plant growth, enhances germination and increases yield in various vegetables, field crops, and ornamentals as well as, it is a sustainable source of macro, and micronutrients and has extensive potentials for enhanced plant growth when used as soil components (Sahni et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sahni et al (2008) have compared the suppression effectiveness of two different approaches, in which two nonconventional chemicals ZnSO 4 and oxalic acid and the bio-control agent Pseudomonas syringae were applied as foliar sprays and seed coating, respectively, with the combination of vermicompost substitution in the potting soil against collar rot of chickpea caused by Sclerotium rolfsii. Vermicompost substitutions provided significant reduction in mortality of chickpea compared to control, but the suppression was more effective with treatments in which preinoculation with the nonconventional chemicals as foliar sprays were applied against the pathogen.…”
Section: Application Of Solid Vermicomposts For Plant Disease Controlmentioning
confidence: 99%